A Controlled Vocabulary and Metadata Schema for Materials Science Data Discovery. (29th April 2021) - Medina-Smith, Andrea; Becker, Chandler A.; Plante, Raymond L.; Bartolo, Laura M.; Dima, Alden; Warren, James A.; Hanisch, Robert J.
The International Materials Resource Registries (IMRR) working group of the Research Data Alliance (RDA) was created to spur initial development of a federated registry system to allow for easier discovery and access to materials data. As part of this effort, a controlled vocabulary and metadata schema were developed with contributions from members of the working group and other experts. Here we describe the process, the resulting vocabulary and XML schema, and lessons learned in the development and use of the schema.